Тhe holographic method for diagnostics of nanoparticles in dense nanosuspensions - V.I. Ivanov; A.V. Myagotin (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов, 2024)
The efficiency of the recording dynamic holograms in dispersed liquid-phase media with a high concentration of nanoparticles is analyzed. The optical nonlinearity of the medium is due to the electrostriction forces acting on the particles of the dispersed phase in a gradient light field. Mass transfer is considered in the case of suprathermal radiation intensities, when the light-induced change in the concentration of nanoparticles is greater than the initial one and reaches saturation. It is shown that at high levels of the radiation intensity, the recording of a dynamic hologram is carried out in a significantly nonlinear mode, when the phase lattice becomes non-sinusoidal. At the same time, the amplitude of the first harmonic increases sharply with increasing intensity, which makes it possible to achieve a significant increase in the efficiency of the hologram recording. The results obtained are relevant for dynamic holography of dispersed liquid-phase media, as well as for optical diagnostics of such media.